Preparation and characterization of methoxy polyethylene glycol-conjugated phosphotriesterase as a potential catalytic bioscavenger against organophosphate poisoning - Jun, Daniel; Musilová, Lucie; Link, Marek; Loiodice, Mélanie; Nachon, Florian; Rochu, Daniel; Renault, Frédérique; Masson, Patrick (Chemico-biological interactions, 2010)
Bioscavengers are considered as promising antidotes against organophosphate poisoning. We focused on a bacterial phosphotriesterase (PTE) expressed in Escherichia coli. The main disadvantage of this non-human catalytic bioscavenger is its relatively short half-life in the organism and strong immunogenicity after repeated administration. Therefore, we prepared different methoxy polyethylene glycol (MPEG)-conjugated recombinant PTE as a potential catalytic bioscavenger with the aim to improve its biological properties. Enzyme was modified with two linear monofunctional MPEG derivatives with reactive aldehyde group of molecular weight 2 kDa and 5 kDa. We optimized reaction conditions (reagent ratios, temperature and duration of modification reaction) and we prepared homogeneous population of fully modified recombinant PTE with molecular weight around 52 kDa and 76 kDa, respectively. Modified PTE was characterized using SDS-PAGE and MALDI-TOF and by determining K(m) and V(max). We also investigated thermal stability of modified enzyme at 37 degrees C. Based on our results, for future in vivo evaluation of pharmacokinetics and pharmacodynamics properties, we selected recombinant PTE modified with 5 kDa MPEG aldehyde for its superior thermal stability.
Keywords: aktivace enzymů; Electrophoresis, Polyacrylamide Gel; antidota; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Hydrogen-Ion Concentration; teplota; Enzyme Activation; otrava organofosfáty; Polyethylene Glycols; Antidotes; Phosphoric Triester Hydrolases; Organophosphates; Aldehydes; biokatalýza; polyethylenglykoly; Temperature; aldehydy; organofosfáty; hydrolasy triesterů kyseliny fosforečné; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Enzyme Stability; elektroforéza v polyakrylamidovém gelu; Biocatalysis; koncentrace vodíkových iontů; Organophosphate Poisoning; Caulobacteraceae; stabilita enzymů